(untitled) (Global Journal of Management and Business Research, 2017)
This research work borders on the motivation and teacher’s effectiveness in the classroom. Research studies have shown that motivation is very vital of workers to put in their best in delivering their services. This work therefore investigates the extent to which the classroom teacher will be effective if adequately motivated. The study focuses on teachers in Ogor Kingdom in Ughelli North Local Government Area of Delta State. To investigate the above mention topic a questionnaire was design in line with the hypothesis formulated to guide the study. The questionnaire was administered to the teachers in Ogor Kingdom and their responses for the basis upon which the date were analyzed. The data obtained were analyzed using percentages. The result showed that: The classroom teacher is not adequately motivated and that the salary and total motivational packages received do not commensurate both the present economy of the nation due to frequent inflation and high standard of living.